Women's Education in Latin America: a decolonial look - Adriane Santana Lima (Universidade Federal do Rio Grande do Sul, 2019)
This article analyzes the conception of education for women that are present in the works of Nísia Floresta and Soledad Acosta, and relates to this conception to the Latin American independence and decolonization movements. It is grounded in decolonial feminist genealogy and methodologically, in cultural and comparative history. The results show that the authors debate the educational formation of women in close relationship with the decolonization political movements of the Latin American continent. Their writings constitute a frontier thought that emerges in the dense web of decoloniality.